An investigation of monolithic nickel-based catalyst for clean hydrogen production with CCS technology: the effect of structure - Shen, Ziqi; Nabavi, Seyed Ali; Clough, Peter T. (Elsevier, 2024)
At present, hydrogen is recognised as a carbon-free energy carrier, but its major production via the steam methane reforming (SMR) process requires further decarbonisation as a considerable amount of carbon dioxide is simultaneously emitted. Carbon capture and storage (CCS) techniques can be integrated with typical SMR to produce clean hydrogen. Previously, a novel structured catalyst (Ni/SiC-M) was developed, and it was highly active for SMR under low operating temperature and high gas space velocity. By integrating CCS techniques, this structured catalyst is promising to produce clean hydrogen, however, there is a lack of knowledge about the catalytic performance when CCS is applied, especially the effect of structure. In this work, the feasibility of producing cleaner hydrogen with monolithic catalysts (Ni/SiC-M) coupled with sorbent particles was discussed. Different modified structures were applied for performance evaluation with a fixed bed reactor, to better understand the relationship between the structure and the activity. The results showed that sorbent particles can adsorb most of the generated carbon dioxide, leading to a higher hydrogen purity; the limitation of internal mass transfer caused by high pressure drops can result in a decrease in catalytic activity, but the impact was limited. The pore size could be the key factor to influence the performance of structured catalysts.
Keywords: Structured catalysts; Structure; Steam methane reforming; Hydrogen production; Carbon capture